(untitled) (The International Journal for Scientific Research, 2023)
The current study aimed to identify the degree to which primary school students possess mental arithmetic skills from the point of view of their teachers, and to identify the mental arithmetic skills that primary school students should possess. The study used the descriptive analytical method and the questionnaire as a tool for collecting data. The study sample consisted of (80) female teachers who were chosen randomly. The results of the study showed that the degree of primary school students’ possession of mental arithmetic skills from their teachers’ point of view was moderate, with an arithmetic mean of (2.7150) and a standard deviation of (0.13570) In light of the results, the researcher recommended training students in mental arithmetic skills and including mathematics textbooks for the primary stage with activities that develop mental arithmetic skills.